Awareness of the Attendants of Primary Health Care Centers about Screening Investigations - Mitwalli, Jawaher Saleh; Sharaf, Nuha Tariq; Bamookrah, Kholoud Mohammed; Badokhon, Amerah Hassan; Albauomi, Rayan Mohammed; Alobaid, Sadah Qamous; Alamri, Manal Hamed (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Screening investigations are group of tests designed to the risks of subsequent disease or early detection of diseases in apparently healthy individuals. Seeking for screening tests is influenced by awareness of the individuals about its importance. The current study aimed at estimating the level of awareness about screening investigations among attendants of the primary health care centers. Methodology: Through a cross-sectional design, 389 attendants were randomly selected form four primary health care centers in Jeddah governorate, they responded to a predesigned questionnaire including items reflecting awareness of the respondents about the importance and types of screening investigations in the primary health care centers. Data entry and statistical analysis were done using Statistical Package for Social Science (SPSS) version (26). The awareness scores were tested for normality using Shapiro Wilk's test, accordingly, for testing significance in difference between two subgroups. Independent sample t test was used, and ANOVA test was used for more than two groups. To detect significant factors predicting the level of awareness, linear logistic regression was used. Statistical significance was set at P-value <0.05 and confidence interval of (95%). Findings: Out of all interviewed participants (n=389), females formed two thirds (68.9%), and the great majorities were Saudis (87.4%) and most of the respondents had university qualifications (79.9%). The overall awareness score accounted for 3.82±0.48 that corresponds to 76.4%. The majority were aware that checking blood pressure 368(94.6%) and blood sugar 343(88.2%) are among the recommended routine medical checkup for individuals. Almost one third undergone previous routine medical checkup (36.7%). The awareness score was significantly higher among females (3.87±0.49), Saudis (3.85±0.48) and highly educated individuals (3.87±0.48) p<0.05. Recommendations: The attendants of the primary health care centers have a good level of awareness about the importance. Types of routine screening investigation, nevertheless, their utilization of these services is suboptimal. The level of awareness was found to be higher in females and highly educated individuals. It is recommended that health education should be provided to the attendants of the primary health care centers focusing on males and the low educated individuals.